Treatment planning for traumatized teeth - Tsukiboshi, Mitsuhiro (Quintessence, 2000)
Increased knowledge of treatment outcomes, combined with better techniques and materials, has led to improved management and more predictable results for victims of dental trauma. To save teeth and restore function and esthetics, the clinical approach to dental trauma requires accurate diagnosis of the severity and extent of injury, treatment of the acute aspect of the injury, and long-term follow-up and treatment of injury sequelae. Each chapter in this book is arranged by: description, examination and diagnosis: key points; treatment plan; and treatment procedures. Described is the biologic basis of healing and the benefits of allowing healing to be used in the management of traumatic dental injuries. Also described are the roles orthodontic and restorative modalities play in the management of dental trauma. More than 50 cases and 480 images - intraoral, radiographic, and schematic - elucidate the most effective approaches to all forms of dental trauma.
Keywords: úrazy zubů; zubní lékařství; Therapeutics; terapie; Tooth Injuries